Competitive Advantage Industri Pariwisata Halal Singapura Dalam Berdaya Saing di Asia Tenggara - Afni Regita Cahyani Muis; Rifda Zulfani Aisyah (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2022)
This research discusses the competitive advantage of Singapore's halal tourism industry in Southeast Asia. The government's efforts to be competitive with regional countries are carried out through innovations in the tourism industry and improvement of various related industries. This study analyzes Singapore's efforts to boost the competitiveness of its halal tourism industry through conceptualizing the Diamond of National Advantages as a derivative from competitive advantage theory 4 pillars, namely: Factor Conditions; Demand Conditions; Related and Supporting Industries; Firm Strategy, Structure, and Rivalry. By using an explanatory qualitative method with a causality approach, this research shows that the Singapore halal tourism industry has opportunity to be competitive through competitive advantage which is reviewed based on the Diamond of National Advantages as a benchmark for the success of the Singapore tourism industry. Meanwhile, to be competitive in the region, Singapore faces challenges from competing countries, such as Malaysia, Indonesia and Thailand.